Anti-mutagenic effects of niacin and nad analogues - Ko, Elizabeth
A study on the antimutagenic and anticlastogenic potential of niacin on an antibiotic, tetracycline hydrochloride, and on two known mutacarcinogens, 3-methylcho;anthrene and methylmethsnesulfonate, was undertaken using the micronucleus test. Various doses of niacin were tested against the mutagens at a dose wherein maximal response on induction of micronuclei in polychromatic erythrocytes was observed. Niacin was administered simultaneously , one hour before and one hour after the mutahen. Antimutagenic effect was found to be dose dependent and was best observed when niacin was given simultaneously with the mutagens. Antimutagenic effect of niacin was most efficient against ,ethylmethanesulfonate, followed by 3-methylcholanthrene, then tetracycline hydrochloride. Analogues of NAD were also tested for their antimutagenic effects on the induction of micronuclei by 3-methylcholanthrene. Their effects did not vary significantly from that exhibited by niacin.